Determinants of unintended pregnancies among currently married women in Uganda - Ronald Wasswa; Allen Kabagenyi; Leonard Atuhaire (BMC, 2020)
Abstract Background Unintended pregnancies are no longer bound to teenagers or school-going children, married women in Uganda, as well do experience such pregnancies though little has been investigated on them. This study examines the determinants of unintended pregnancies among currently married women in Uganda. Methods In this study, we used data from the 2016 Uganda Demographic and Health Survey (UDHS) which comprised of 10,958 married women aged 15-49 years who have ever been pregnant. The analysis was done using descriptive analysis, logistic regression, and the generalized structural equation model. Results The study showed that 37% of pregnancies among married women were unintended. Young women, living in poor households, staying in rural areas, women in the Eastern and Northern region, Muslim women, lack of knowledge on ovulation period, discontinuation of contraceptives, non-use of and intention for contraceptives, high age at sexual debut, high age at first birth, and high parity were directly associated with a higher risk of unintended pregnancies. Relatedly, discontinuation of contraceptives regardless of the place of residence, region, woman's age, education, household wealth, access to family planning messages were associated with higher odds of unintended pregnancies. Older women and those in rural areas who had more children were also at a higher risk of similar pregnancies. However, having more children while using contraceptives, being educated, living in a wealthier household, and having access to family planning messages significantly lowered the risk of unintended pregnancies. Conclusion Increased access to family planning messages, empowering women as well as having improved household incomes are key preventive measures of unintended pregnancies. There is a need to provide quality contraceptive counseling through outreaches so that women are informed about the different contraceptive methods and the possible side effects. Having a variety of contraceptive methods to choose from and making them accessible and affordable will also encourage women to make informed choices and reduce contraceptive discontinuation. All these coupled together will help women have their desired family sizes, increase the uptake of contraceptives and significantly reduce unintended pregnancies.